The use of Information technology at BUAN Library by beef production farmers in Lobatse-Botswana - Letshabo, Lilian Mmapula (Library and Information Studies Centre (LISC), 2025)
This study examines the use of information technology by beef production farmers in Lobatse, Botswana. This study aimed to explore the role of library-based IT services in enabling access to information on best practices for beef production, market prices and trends, disease management, and other relevant topics. It also examined the training and support provided to farmers using library-based IT services, including digital tools for record-keeping, analysis, and decision making, as well as their familiarity with digital platforms and resources. Moreover, this study examined opportunities for collaboration and networking among farmers, researchers, and extension workers using library-based IT services. The study adopted a pragmatic paradigm, whose worldview focuses on what works rather than what might be considered valid or accurate. This study is based on the belief that technology is available, but an investigative approach establishes what beef production farmers consider usable, and the basis upon which that usability is based. Coupled with this paradigm, this study considers the Technology Acceptance Model (TAM) as an appropriate theoretical framework. This study adopted a multi-method technique that employed both qualitative and quantitative data collection methods, in which data collection was performed concurrently. The qualitative approach was used to collect data from the BUAN Library Client Services Unit staff, whereas the quantitative approach was used to collect data from traditional and commercial beef production farmers in Lobatse, south-eastern Botswana. Data were collected using questionnaires and structured interviews. Questionnaires were administered to beef production farmers in Lobatse, and interviews were conducted with BUAN Library Client Services Unit staff. Quantitative data were analysed using descriptive statistics and presented in tables, graphs, and charts using the Statistical Package for the Social Sciences (SPSS), while qualitative data were analysed using Microsoft Excel. The findings emanating from both the qualitative and quantitative data collected demonstrated that, although farmers use information technology to support beef production, it is minimal owing to the lack of interest, relevant expertise in information technology services, and perceived usefulness of the technologies. However, some farmers showed a willingness to use more advanced information technology tools if given support and training from agricultural institutions in Botswana. This study provides insights into the challenges and opportunities of library-based IT services in the agricultural sector in Botswana and other developing countries. This study highlights the significance of library-based IT services in providing access to information and promoting digital literacy and skill development among beef production farmers, thereby enhancing their overall productivity and contributing to the agricultural sector development. Recommendations from the study suggest an engagement between stakeholders and local communities as an avenue for deep learning inclined towards sustainable social change and for the library to focus on teaching and demonstrating available IT tools by promoting their usability to farmers regularly.